EFEKTIVITAS PENGELOLAAN PT. PRPP JAWA TENGAH - Stefanus Henry Christiawan; Warsito .; Wahid Abdulrahman (Journal of Politic and Government Studies, 2017)
PT. PRPP Central Java is one of the BUMD of Central Java Province that manages the PRPP and Grand Maerakaca areas. As a BUMD PT. PRPP Central Java has an obligation to pay dividends to the Central Java provincial government. In the period 2012-2015, PT. PRPP Central Java is still not able to provide dividends to the Central Java Provincial Government. The purpose of this study is to determine the effectiveness of the management of PT. PRPP of Central Java and the factors that caused PT. PRPP Central Java has not been able to provide dividends to the Central Java Provincial Government.The research method used is qualitative research with data collection technique that is observation, interview, document, and audio-visual material. Informant in this research is board of PT. PRPP Central Java, employees of PT. PRPP Central Java, Head of Sub Division of PID and BUMD of Central Java Province, and the people of Semarang City.The results showed that the effectiveness of PT. PRPP Central Java has been quite effective seen from the three indicators of quality, productivity, and growth. Factors that cause PT. PRPP Central Java has not been able to provide dividends to the Central Java Provincial Government is the change of management from the foundation to the form of Limited Liability Company, limited working capital for the development of the company. Recommendations that can be addressed to PT. PRPP Central Java is to maximize the assets of PRPP and Grand Maerakaca by building new facilities and organizing interesting events.Keywords: Management Effectiveness, PRPP Jawa Tengah Corporation